Nursing Roles In Enhancing Patient Safety And Reducing Hospital-Related Complications: A Systematic Review (The Review of Diabetic Studies, 2024)
Background: The global healthcare landscape addresses the persistent challenge of preventing harm during clinical care. Hospital-acquired complications (HACs)—encompassing healthcare-associated infections (HAIs), pressure injuries, falls, and failure to rescue deteriorating patients—represent a significant burden on patient morbidity, mortality, and healthcare economics. Nurses, as the primary surveillance agents within the hospital system, are uniquely positioned to mitigate these risks through continuous monitoring, intervention, and system coordination.Objective: This systematic review aims to comprehensively evaluate the multifaceted roles of nursing in enhancing patient safety and reducing hospital-related complications. The review specifically investigates the impact of structural variables (nurse staffing ratios and education) and process variables (nurse-led clinical care bundles and Rapid Response Teams) on patient outcomes. A dedicated focus is applied to the healthcare context of the Middle East to identify region-specific barriers and facilitators to safety.Methods: A systematic synthesis of literature was conducted, reviewing studies primarily published between 2014 and 2023. The review categorizes evidence based on Condition: Hospital-Acquired Complications and Population: Adult and Pediatric Inpatients.Results: The analysis reveals a robust causal linkage between nurse staffing levels and patient safety outcomes, with lower nurse-to-patient ratios consistently associated with reduced mortality and adverse events. Nurse-led clinical interventions, specifically the "care bundle" approach for pressure ulcers (HAPU) and infections (CLABSI, VAP), demonstrated significant efficacy in reducing complication rates when adherence is high. In the domain of system-wide safety, the implementation of nurse-led Rapid Response Teams (RRT) in tertiary hospitals was associated with a dramatic 48% relative risk reduction in inpatient mortality. However, the review identifies critical barriers in the regional context, including the prevalence of defensive nursing practices, punitive organizational cultures regarding error reporting, and significant resource constraints.Conclusions: Nursing roles act as the linchpin of patient safety systems. The evidence suggests that optimizing nurse staffing, enhancing education on evidence-based practices, and fostering a non-punitive safety culture are prerequisite steps for reducing hospital-related complications. The "COVID-19 paradox" observed in infection rates further underscores the critical importance of adherence to basic safety protocols.